THE ANALYSIS OF ENGLISH LANGUAGE EDUCATION STUDENTSâ TEACHING SKILLS DURING MICROTEACHING: PRODUCT-PROCESS APPROACH IN TEACHING GRAMMAR - Agustin, Atalya (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
Teaching grammar within the context of Second Language Acquisition (SLA) needs both product and process approaches. Microteaching is one of the techniques to prepare students teachers to improve their skills in this area. One of the microteaching lessons in English Language Education Department, Teachers College Universitas Pelita Harapan, is called Planning, Strategy, Assessment, and Learning (PSAL) Grammar. In this class, students are exposed with the nature, principles, and strategy of teaching and learning grammar. Students are planning lessons related to teaching grammar in various grades as well as developing teaching and learning material and instrument for language assessment. Students then put them into practice in the classroom individually. Discussion on the students âperformances will be conducted after the microteaching session. This research aims to analyze studentsâ skills in teaching grammar in microteaching class as well as the discussing the strength and challenges arise. The type of the research is a qualitative case study research. The data collection techniques being used are observation, reflective journal, and Focus Group Discussion (FGD). Moreover, the technique of analyzing the data was Miles and Huberman concept of data reduction, data presentation, and conclusion drawing. The results of this research will be presented in a descriptive-narrative manner by describing and discussing studentsâ skills in teaching grammar.Â